The dangers of Bullying and sexual harrasement: Bahaya Anti Penindasan dan Pecehan Seksual - Siti Nor Elisa; Dzul Rachman; Shabrina Nur Fadillah; Muhammad Adzha Yoanduanda; Nurfani Yulianti; Rizky Ramadhi; Nur Alamsyah (Wadah Inovasi Indonesia, 2023)
Students of the 2021 Sports Education and English Education Study Programs have carried out Real Work Lecture (KKN) program activities on July 23 - September 26, 2024 in the environment of SMA Negeri 15 Samarinda. This program is one of the courses that must be taken by students of the Faculty of Teacher Training and Education (FKIP) before going directly into the world of education. This KKN activity aims to develop creativity and build cooperation between students, teachers, students and other school residents. There are 3 activities that must be carried out while at SMA Negeri 15 Samarinda, namely the collaboration of students and OSIS SMA Negeri 15 Samarinda to make the August 17 Competition and the Seminar “The Importance of Higher Education” and “The Dangers of Bullying and Sexual Harrasment”. As for the optional activities, there are 3, namely the making of a “Mini Park” which is divided into 3 parts, namely the making of a mini park, a cleanliness sign and also submitting a plant request proposal to the Samarinda City Environmental Service, making Anti-Bullying and Sexual Harassment posters.